"Boundaries Bind Unbinding": Jazz and Cold War Cosmopolitanism in the Margins of Langston Hughes's Ask Your Mama. (1st March 2021) - Schuster, Adam
Abstract: While Langston Hughes is typically read as a staunch supporter of solidarity defined by descent, I suggest that his 1961 poem Ask Your Mama pursues a form of sociality that privileges race but is not exclusively determined by it, instead exploring possibilities for cosmopolitan exchange. As the negotiation of alterity and the reexamination of inherited attachments—cultural, racial, or national—cosmopolitanism is a crucial although understudied radical strain of thought in this moment, and one we can hear sounded in Hughes's jazz poem. Hughes's column for the Chicago Defender displays traces of a cosmopolitan ethos leading up to the composition of Ask Your Mama, traces that coincide with the transnational values inspired by jazz's increasingly international circulation. Drawing on the surge in music's postwar commercial and state-sanctioned circulation, Hughes's poem becomes a unification of his own impulse to expand affiliations across national and ethno-racial lines and the discourses around jazz and other vernacular music. Ask Your Mama combines generic forms and overlays scales of exchange that exceed any neatly defined geographic origin or cultural category. Analyzing these combinations of poetry and music, I show how networks of alternative meanings are produced that reconfigure relations between geographic distance, community, and identity, the comingling of disparate cultures and national affiliations formalized in the interstices of music and poetic verse. Ultimately, Hughes demonstrates how, amid the overlapping seizures and resignifications of black cultural production at mid-century, jazz music could be reclaimed and repurposed to transform poetry's structure and rearticulate the boundaries of ethno-racial solidarity.